Costos y gastos de la Empresa Adolti S.A. de la ciudad de Guayaquil en el periodo 2021-2022. - Zúñiga Cortez, Miguel Ángel (2024)
The case study "Costs and Expenses of Adolti S.A. in Guayaquil during 2021-2022" explores the financial challenges encountered by Adolti S.A., a road transport company, primarily due to high costs and expenses that impact its profitability. The general objective is to understand the underlying causes of increased costs and expenses to inform decision-making for enhanced efficiency and profitability. The primary issue identified is the significant rise in raw material costs, driven by inflation, exchange rate fluctuations, and supply chain disruptions. Additionally, general expenses, such as rents, utilities, and administrative costs, have increased. The methodology involves a thorough review of the company's financial data, employing financial indices to assess efficiency and identifying key areas for improvement. Data collection was done through financial records analysis, and the information was synthesized to propose strategies for cost reduction. Key findings include the identification of inefficiencies in cost management and opportunities for improvement. For instance, negotiating with suppliers and automating processes can significantly reduce costs. The conclusions emphasize the importance of detailed cost and expense control for long-term sustainability and profitability. Recommendations include reviewing internal spending policies, implementing better cost management practices, and exploring technological solutions to streamline operations.